Detection of Wuchereria bancrofti in the city of São Luís, state of Maranhão, Brazil: New incursion or persisting problem? - Araújo, Tatiane Alexandre de; Lima de Albuquerque, Alessandra; Melo, Danielle Cristina Tenório Varjal de; Santos, Eloína Maria de Mendonça; Oliveira, André Luiz Sá de; Ayres, Constância Flávia Junqueira; Oliveira, Cláudia Maria Fontes de (PLOS Neglected Tropical Diseases, 2023)
Author summary In the diagnosis of lymphatic filariasis (LF) using molecular xenomonitoring, the collection of mosquitoes is a critical step. Catching insects within the residence after the blood meal is ideal because the use of engorged or gravid females increases the odds of finding the parasite ingested during a meal and indicates the occurrence of microfilaremia patients in the region. In São Luís, more than ten thousand adult mosquitoes were removed from the residences in the study period. Considering the confirmation of the pools of Wuchereria bancrofti-infected C. quinquefasciatus females, it is necessary to initiate chemotherapeutic treatment to avoid the recrudescence of LF. Several cities in Brazil have environmental and socioeconomic profiles similar to those found in São Luis, especially those that were considered endemic for LF at some time in the public health history of the country. The collection and diagnostic methods used in the present study can and should be used in other Brazilian states for verifying the interruption of LF transmission.